IDENTIFICATION OF RAPD MARKERS LINKED TO MYMV RESISTANCE IN MUNGBEAN (VIGNA RADIATA (L). WILCZEK) - PRAVEEN HOLEYACHI; D. L. SAVITHRAMMA (The Bioscan, 2013)
The present study was undertaken to identify random amplified polymorphic DNA (RAPD) marker associated with mungbean yellow mosaic virus (MYMV) resistance in mungbean (Vigna radiata (L). Wilczek) by employing bulk segregant analysis in recombinant inbred lines (RILs). Out of 20 random decamers, only ten primers viz; OPA-03, A-06, A-03, OPA-09, A-09, OPB 7, UBC-391, OPC-08, UBC 499 and A-04 showed polymorphism between parents Chinamung and BL 849. Out of these ten primers only one primer i.e. UBC 499 amplified a single 700 bp band in the genotype BL 849 (resistant parent) and MYMV resistant bulk which was absent in Chinamung (susceptible parent) and MYMV susceptible bulk. PCR amplified 700 bp marker band was detected in individuals of F5 RILs constituting the MYMV resistant bulk indicating that primer UBC 499 was linked to MYMV resistance. This marker can be used in screening mungbean genotypes for resistance to MYMV disease.